2013
DOI: 10.1097/ede.0b013e3182877eb8
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding as a Modifier of the Respiratory Effects of Air Pollution in Children

Abstract: Breastfeeding is associated with smaller associations between air pollution and respiratory conditions in children, suggesting that breastfeeding reduces susceptibility to the respiratory effects of pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
1
38
2
Order By: Relevance
“…Interestingly, we found that a history of breastfeeding was associated with increased odds of wheeze in girls while this was protective in boys, both with a history of parental atopy. While most studies have documented a protective role of breastfeeding for wheeze and asthma or that breastfeeding attenuates the effect of other risk factors for asthma, others suggest that breastfeeding has no effect or is a risk factor for future asthma, especially in children with a parental history of asthma . Other than methodological differences, these conflicting findings may reflect the variability in breast milk composition depending on maternal factors such as atopy, diet, metabolism, and environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that a history of breastfeeding was associated with increased odds of wheeze in girls while this was protective in boys, both with a history of parental atopy. While most studies have documented a protective role of breastfeeding for wheeze and asthma or that breastfeeding attenuates the effect of other risk factors for asthma, others suggest that breastfeeding has no effect or is a risk factor for future asthma, especially in children with a parental history of asthma . Other than methodological differences, these conflicting findings may reflect the variability in breast milk composition depending on maternal factors such as atopy, diet, metabolism, and environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Wave 1 was during a period from 2008 to 2009, and Wave 2 was conducted from 2012 to 2013. Wave 1 was conducted to assess the relationship of outdoor and indoor air pollution with asthma and asthma‐related symptoms in children using among 31 049 children from 25 districts of the seven cities in Northeastern China . Wave 2, which occurred in 2012‐2013, was conducted to evaluate the effects of air pollution on lung function, blood pressure, and mental health, including attention deficit hyperactivity disorder (ADHD) and sleep disorder .…”
Section: Methodsmentioning
confidence: 99%
“…It contains a number of anti‐infectious agents that protect infants from the invasion of certain pathogens. In particular, breastfeeding influences the programming of aberrant patterns of both immunological memory specific for inhaled allergens and the inflammatory damage to the lung and airway tissue that occurs during the critical stage of growth in early childhood (Dong et al., ; Sly and Holt, ). Substantial evidence shows that breastfeeding is associated with a reduced risk of childhood respiratory diseases (Ajetunmobi et al., ; Al‐Makoshi et al., ; Rosas‐Salazar et al., ; Yamakawa et al., ) and a decrease in the effects of other environmental factors including ETS on health (Baker et al., ; Chulada et al., ; Woodward et al., ).…”
Section: Introductionmentioning
confidence: 99%